Towards a generalized model of diagnostic behaviour - Johnson, Leslie; Keravnou-Papailiou, Elpida (My University, 1989)
A model of diagnostic behaviour shared by most diagnostic tasks is discussed. The model is, by-and-large, presented at a conceptual (knowledge) level. Its expression at more concrete level is task dependent. The model's use can be seen as being twofold: first as an aid in the construction of more adequate shells for diagnostic tasks; and second, and more importantly, as the initial (albeit crude) interpretation model held by the knowledge engineer about to embark on the cumbersome task of analysing a particular expert diagnostician's behaviour
Keywords: Expert systems (Computer science); Computer science; Medicine; Diagnosis